Multiplexed immunoassay-based serum cytokine profiling for potential prognosis predictors in patients with metastatic breast cancer - Huang, Hongyan; Zhang, Yanbin; Li, Sha; Zhao, Jing; Wang, Xiaoli; Zhou, Xinna; Ren, Jun (Translational Cancer Research, 2018)
Background: Although the patients suffering from metastatic breast cancer (MBC) have experienced considerably wide survival ranges, reliable biomarkers for its prognosis have remained unidentified. This study attempted to profile the serum cytokine candidates that could potentially be used to predict the prognosis of MBC patients. Methods: By using the ProcartaPlex Multiplex Immunoassay, a total of 45 cytokines were assayed in sera from 18 MBC patients before any treatment. Results: Thirty-three types of cytokines were cross-detectable in more than 50% of the patients and thus were acceptable for a further analysis. Univariate analysis uncovered 10 sera cytokines significantly associated with MBC patient death. Among them, interleukin 8 (IL-8), fibroblast growth factor (FGF2), hepatocyte growth factor (HGF) and VEGF-A were reported, and 6 cytokines which included NGF-β, IFN-γ, IP-10, IL-18, MCP-1 and MIP-1β were identified for the first time as MBC death-correlated serum factors. Conclusions: Identification of these cytokines would facilitate developing novel serum biomarkers for MBC, favoring multiplexed serum cytokine profiling a promising method in predicting the outcome of MBC patients.